Determining how almond (Prunus dulcis) harvest and processing contributes to low levels of glyphosate and glufosinate residues in almonds. Issue 1 (23rd January 2023) - Martin, Katie; Hanson, Bradley D.
Abstract: California is the top producer of almonds [ Prunus dulcis (Mill.) D.A. Webb] worldwide, generating more than $6 billion in revenue in 2020; the European Union (EU) is the primary importer of California almonds. Weed control in almond orchards is an important part of the preharvest process, because weeds can interfere with harvest equipment and host diseases. Glyphosate and glufosinate are broad-spectrum herbicides commonly used for preharvest weed control. Global differences in maximum residue limits (MRLs) and regulated compounds can pose a challenge for growers who rely on broad-spectrum herbicides such as glyphosate and glufosinate for preharvest weed control. The EU MRL for glyphosate and total glufosinate is currently 0.1 mg kg −1 . The U.S. MRL for total glyphosate is 1 mg kg −1, and total glufosinate is 0.5 mg kg −1 . An 8-wk field experiment, from spray to harvest, was conducted in an 8-ha commercial orchard to evaluate the potential contribution of the preharvest herbicide treatment to low levels of herbicide residue in almonds. Then, the same batch of almonds was followed through a commercial processing facility to evaluate the potential movement of herbicide residues from soil, debris, and hulls to almond kernels during processing. Glyphosate was not detected in any almond kernel samples at the end of processing. A glufosinate metabolite, 3-(methylphosphinico)propionic acid (MPP), was detected in kernels at the end of processing at about 0.1 mg kg −1, which is above the EU MRL for total glufosinate. Almonds sampled directly from the tree, without any contact with soil, were found to have elevated MPP residues. This indicates glufosinate or MPP translocation may be a factor in low-level glufosinate residues detected in almonds in some EU exports.